2011
DOI: 10.1108/09604521111185628
|View full text |Cite
|
Sign up to set email alerts
|

Customer service understanding: gender differences of frontline employees

Abstract: PurposeDespite widespread acknowledgement of the importance of employees to the success of service firms, research into how well frontline service staff understand service remains scarce. This study aims to investigate what constitutes good customer service from the viewpoint of frontline service employees and to explore gender differences in particular.Design/methodology/approachThe data were collected from 876 frontline employees across a wide range of service industries. An automated text analysis using Lex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 36 publications
0
38
3
1
Order By: Relevance
“…Leximancer conducts both conceptual (thematic) and relational (semantic) analyses of text data and then provides visual depictions of these analyses. It allows the researcher to examine concepts (common text elements) and themes and contradictions (groupings of uncovered concepts) used by other scholars (Mathies & Burford, 2011). To do so, a Bayesian machine-learning algorithm is applied to uncover the main concepts in text and how they relate to each other (Campbell et al, 2011).…”
Section: Textual Analysis/data Miningmentioning
confidence: 99%
“…Leximancer conducts both conceptual (thematic) and relational (semantic) analyses of text data and then provides visual depictions of these analyses. It allows the researcher to examine concepts (common text elements) and themes and contradictions (groupings of uncovered concepts) used by other scholars (Mathies & Burford, 2011). To do so, a Bayesian machine-learning algorithm is applied to uncover the main concepts in text and how they relate to each other (Campbell et al, 2011).…”
Section: Textual Analysis/data Miningmentioning
confidence: 99%
“…Between these dimensions, our findings in the retail context infer that male employees are more oriented to professional relations, while female employees are more oriented to social relations. This also corresponds to research in customer service noting that women are process-oriented while men are outcome-oriented (Iacobucci and Ostrom, 1993;Mattila et al, 2003;Mathies and Burford, 2011).…”
Section: Discussion and Modelmentioning
confidence: 85%
“…On the other, this implies that employees can potentially be stereotyped or discriminated against based on the simple observation of their gender. Mathies and Burford (2011) found that the interpretation of good customer service is influenced by the gender of the employee, noting that customers may expect, and respond better to staff of the 'appropriate' gender.…”
Section: Resultsmentioning
confidence: 97%
“…Mathies and Burford (2010), in a sample of 876 frontline employees from a wide range of industries in Australia found, that females had a significantly higher service orientation than did males. Using automated text analysis for responses to an open-ended question ("What do you think is good customer service?…”
Section: Gender Differencesmentioning
confidence: 97%